The analysis of the use of satire in the daily show with Trevor Noah - Rahma, Sitti; Lubis, Syahron; Perangin-angin, Alemina (Englisia Journal, 2023)
Various TV channels established with various talk shows stand out among other shows for presenting bitter facts in a very light-hearted way by commenting, satirizing, analyzing and criticizing in a very funny style. "The Daily Show with Trevor Noah" is a very popular comedy talk show in the United States because of its high language, witty praise, and especially the characters of "The Daily Show with Trevor Noah" criticizing various aspects of society. The aims of this study are to categorize various types of satire and reveal Trevor Noah's technique in expressing satire. This study uses a qualitative descriptive design with a sample of six episodes of The Daily Show with Trevor Noah downloaded from the official comedy center website. The data concentrated on the Satire utterances of the host of The Daily Show with Trevor Noah were analyzed using interactive analysis. The results of the analysis showed that three types of satire appeared in the event: 21 Horatian satires, 13 juvenile satires, and 16 Menippean satires. The satire that is used in the daily show has conveyed a message of criticism of someone's ideas and behavior based on what they have said and done based on events that actually happened. Sacrificial conclusions have become the most powerful and effective way of getting a message across, even today, no matter what means a satirist chooses to create their work.